(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the pedagogical significance, methodological foundations, and practical possibilities of integrating STEAM technology and the meta-subject approach in the primary education system. In the modern educational process, developing students’ creative thinking, independent inquiry, problem-solving abilities, and practical activity skills is considered an important task. From this perspective, STEAM education and the meta-subject approach are becoming significant factors in helping students acquire interdisciplinary knowledge and develop essential life competencies. The article also highlights methods for organizing integrated lessons for primary school students, the role of the teacher, as well as existing problems and their possible solutions.